Cooperation for development : an analysis of Chinese investments in Brazil’s energy sector (2010-2018) - Kotz, Ricardo Lopes (Seminário Pesquisar China Contemporânea, 2021)
Energy constitutes the biggest sector in which China has invested in Latin America, accounting for 51% of Chinese investments in the region between 2007-2018. In the same period, Brazil has attracted 70% of Chinese investments made in the energy sector in Latin America (CEBC, 2018, p. 23-24). The present research will focus on the years of 2010-2018, following the end of Luiz Inácio Lula Da Silva’s presidency in Brazil and into the subsequent presidential mandates of the country. The research will be conducted through the use of case study methodology, analyzing two study cases of investments conducted by State Grid Corporation of China.. The first chapter presents the theoretical concepts regarding international cooperation and cooperation for development. The second chapter presents an overview of the relations between China and Brazil, focusing on the dimensions of foreign policy and Chinese FDI. The third chapter verses on the expansion of China’s international presence and its outward foreign direct investments, presenting the Going Global strategy and the Belt and Road Initiative. The third chapter also focuses on the two study cases analyzed: 1) the acquisition of CPFL Energy in 2017, a provider of energy operating in the most important economic region of Brazil; 2) the construction of two transmission lines connecting the Belo Monte Hydropower plant in Northern Brazil to the Southeastern states Minas Gerais, Rio De Janeiro and São Paulo. The main goals of the research are to outline the scenario of energy cooperation between China and Brazil, aiming to investigate what are the main characteristics of the investments conducted by the State Grid Corporation of China. The results point to the fact that Chinese FDI incoming in Brazil have been growing due to the increasing international presence of the country, which corresponds to its initiatives such as Going Global and the BRI. The energy sector is strategic for China due to Brazil’s large potential and resources, such as the Amazonian region and its abundant rivers. Chinese investments can help foster development in the country since they build critical infrastructure which is currently lacking. From the perspective of State Grid such investments are strategic because the company is positioning itself very competitively in a large market. According to State Grid itself, as of the end of 2019, 60% of the company’s investments abroad had been made Brazil.